Multi-objective Optimization of the NN Type Transmission with Small Tooth Difference - Zheng Jianrui; Deng Xing; Li Zhe; Yang Zaiming; Wu Teng; Du Jinze; Zhuo Jiaxin (Jixie chuandong)
Focusing on the demand of energy and heavy machinery for high efficiency and high output capacity of transmission equipment, this research studies the multi-objective optimization of the NN type small tooth difference transmission with the highest efficiency and maximum output capacity. Firstly, traverse all tooth number combinations in the optimization space under different tooth number difference, different staggered tooth difference in a certain range of teeth, and get the tooth combinations table. Then, the multi-objective optimization model of the NN type small tooth difference transmission is established, taking the number of teeth combination, standard pressure angle, meshing angle, addendum height coefficient and displacement coefficient as the optimization design variables and considering the overlap ratio, tooth profile overlap interference and addendum thickness constraints. The multi-objective differential evolution algorithm based on Pareto is used to solve the optimization model, and the distribution of Pareto optimal solution set is obtained. The results obtained in this study are compared with those in the standard design manual. The comparison results show that the results in this study are better than those in the standard design manual, which can provide reference for the design of NN type small tooth difference transmission.